Tinjauan Yuridis Terhadap Putusan Pengadilan Negeri Jakarta Pusat Nomor 759/PDT.G/2023/PN JKT.PST - Rayi Kharisma Rajib; Nauval Athalah Ramadhani; M Zidan Ramadhan (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Inheritance disputes are frequently intertwined with the legal classification of property acquired within marriage, which directly affects the determination of parties’ rights. Case Number 659 Pdt G 2023 PN Jkt Pst reflects a conflict between personal claims of relationship and formally recognized family structure, compounded by the absence of a clearly defined disputed property. This study aims to examine the judicial decision through a doctrinal legal analysis in order to assess the accuracy of the court’s reasoning from both procedural and substantive perspectives. The research employs a normative juridical method using statutory, conceptual, and case approaches, with judicial decisions serving as the primary source of analysis. The findings indicate that the court correctly applied procedural law by declaring the claim inadmissible due to obscurity of the lawsuit, yet the reasoning remains limited as it does not sufficiently elaborate on inheritance law and marital property regimes. This limitation creates potential legal uncertainty since the dispute is not substantively resolved.